DETERMINATION OF REFERENCE VALUES FOR TREC AND KREC IN DRY BLOOD SPOTS OF NEWBORNS FROM DIFFERENT GESTATION AGES IN SVERDLOVSK REGION - S. S. Deryabina; I. A. Tuzankina; V. N. Shershnev (Медицинская иммунология)
As a preparatory stage for implementation of genetic testing for severe combined immunodeficiency under a neonatal screening program, a study was performed in Sverdlovsk Region which concerned quantitative determination of T and B cell neogenesis markers (TREC and KREC, respectively) in blood of conditionally healthy newborns. Archived samples of dry blood spots collected in test-forms for routine neonatal screening were used as biological material for the study of full-term 26 girls and 26 boys who did not exhibit serious illnesses during first year of their life. In addition, we investigated potential effects of foetal gestational age upon the number of TREC and KREC in preterm infants. Blood samples from 55 preterm infants (23 to 36 gestational weeks) were also examined. It was shown that the levels of TREC and KREC increased sequentially with the increased gestation terms, but the quantitative changes of markers showed different dynamics. In this respect, the recommended terms of blood sample collection for SCID screening is entirely consistent with timing of blood sampling for routine newborn screening. An alternative result was obtained with a complete absence of TREC or KREC in blood sample of a newborn, irrespectively of prematurity degree (at valid copy numbers of a control gene) which should serve as an indication for immediate consulting of the child by immunologist and in-depth immunological examination, because it may be a first prognostic sign of a fatal disease. In order to obtain correct cut-off levels for TREC/KREC, additional studies are needed on a larger sample of newborns (1.000 to 5.000), followed by validation of the obtained reference boundaries in studies involving patients with different forms of primary immunodeficiencies.